2020
DOI: 10.1016/j.isci.2020.101638
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Keap1 Confers Features of a Fasted Metabolic State

Abstract: Summary Transcription factor nuclear factor erythroid 2 p45-related factor 2 (Nrf2) and its main negative regulator, Kelch-like ECH-associated protein 1 (Keap1), are at the interface between redox and intermediary metabolism, allowing adaptation and survival under conditions of oxidative, inflammatory, and metabolic stress. Nrf2 is the principal determinant of redox homeostasis, and contributes to mitochondrial function and integrity and cellular bioenergetics. Using proteomics and lipidomics, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 85 publications
2
21
0
Order By: Relevance
“…Srxn1 , another NRF2 target gene, was also marginally upregulated in MK mice. One of the enzymes catalyzing β-oxidation of FAs, Acox2 , was found to be remarkably increased in MK mice compared with Cntl mice, which is consistent with the findings of a recent report describing that Acox2 is a target gene of NRF2 [ 34 ].…”
Section: Resultssupporting
confidence: 90%
“…Srxn1 , another NRF2 target gene, was also marginally upregulated in MK mice. One of the enzymes catalyzing β-oxidation of FAs, Acox2 , was found to be remarkably increased in MK mice compared with Cntl mice, which is consistent with the findings of a recent report describing that Acox2 is a target gene of NRF2 [ 34 ].…”
Section: Resultssupporting
confidence: 90%
“…Because Gstp is involved in xenobiotic metabolism 28 as well as cell signaling, by sequestering c-Jun N-terminal kinase (JNK) 29 , we first asked whether deletion of Gstp affects the Nrf2-mediated transcription using the classical Nrf2-target NAD(P)H:quinone oxidoreductase 1 (Nqo1) as a marker, which is expressed in an Nrf2-dependent manner in the mouse colon 30 . The mRNA levels for Nqo1 in the colon tissues did not differ between Gstp +/+ and Gstp −/− animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using LC-MS analysis of metabolites in colon tissue extracts, we recently found that the levels of glucose 6-phosphate and fructose 6-phosphate, metabolites involved in the initial steps of glycolysis, were higher in colons of Keap1-KD mice in comparison with their WT counterparts, whereas dihydroxyacetone phosphate and glyceraldehyde 3-phosphate, which are involved in the later steps of glycolysis, were lower 30 . Additionally, gas chromatography-MS (GC-MS) analysis showed that the levels of saturated and mono-unsaturated fatty acids were lower in Keap1-KD mice, whereas the levels of polyunsaturated fatty acids were higher.…”
Section: Discussionmentioning
confidence: 99%
“…1f, Supplementary Table S1). Moreover, there exists independent published evidence that all of the 20 genes are direct Nrf2 targets [24][25][26][27][28] . We also confirmed that the tBHQ-induced expression of a selection of genes-Hmox1, Srxn1, and Slc7a11, was strongly abrogated in Nrf2-deficient cultures ( Fig.…”
Section: Tbhq Induces Nrf2-independent Induction Of Jun and Neurotoximentioning
confidence: 99%